2019
DOI: 10.1093/asj/sjz259
|View full text |Cite
|
Sign up to set email alerts
|

Making the Subjective Objective: Machine Learning and Rhinoplasty

Abstract: Background Machine learning represents a new frontier in surgical innovation. The ranking Convolutional Neural Network (CNN) is a novel machine learning algorithm that helps elucidate patterns and features of aging that are not always appreciable with the human eye. Objectives The authors sought to determine the impact of aesthetic rhinoplasty on facial aging employing a multidimensional facial recognition and comparison soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 10 publications
1
41
0
Order By: Relevance
“…2 ). 27 AI models were frequently burdened by phase 0 limitations related to data, statistical performance, and workflow (n = 26) or phase 1 limitations related to technical performance and safety (n = 28). However, many studies were limited by multiple factors from various limitation phases (mean limitations per study = 3.11, n = 44).…”
Section: Resultsmentioning
confidence: 99%
“…2 ). 27 AI models were frequently burdened by phase 0 limitations related to data, statistical performance, and workflow (n = 26) or phase 1 limitations related to technical performance and safety (n = 28). However, many studies were limited by multiple factors from various limitation phases (mean limitations per study = 3.11, n = 44).…”
Section: Resultsmentioning
confidence: 99%
“…27,28 Diminished skin elasticity, atrophy of support structures, and ossification of the fibrocartilaginous framework may contribute to changes in nasal morphology associated with aging, which can be addressed through rhinoplasty. 27,28 Through implementing a Convolutional Neural Network algorithm, Dorfman et al 29 similarly established that aesthetic rhinoplasty conferred reductions in perceived age in an exclusive cohort of female patients. However, it is important to note that this study had a relatively short follow-up period (29 weeks), and thus, postoperative swelling could have impacted conclusions about the role of rhinoplasty on perceived age.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 37 , 39 , 40 , 46 , 51 , 53 , 59 , 63 Further, in conditions in which there are well-established correlations between certain risk markers and an outcome of interest, such as deranged blood tests on admission and AKI in burn patients, ML yielded highly accurate predictive algorithms. 38 , 44 , 55 24 47 However, attempts to include weakly related risk markers resulted in algorithms that had an overall lower predictive accuracy, rendering them unsafe for clinical practice. This review further identified that some plastic surgery subspecialties, such as hand surgery, have yet to incorporate this technology.…”
Section: Discussionmentioning
confidence: 99%